Using Homophone Game to Improve Students' Pronunciation at Junior High School 5 of Tidore Archipelago - S Syamsia; Manawia Salamat (Program Studi Pendidikan Bahasa Inggris, ISDIK Kie Raha Maluku Utara, 2019)
This study was conducted to examine the effect of homophone game towards the students’ pronunciation improvement. Designed as a classroom action research, this study took place in the state junior high school 5 of Tidore archipelago. The researcher involved 20 students as the participants of the research. Through two cycles, the analysis of the data indicated that homophone game could improve the students’ pronunciation.